Impact on growth, oxidative stress, and apoptosis-related gene transcription of zebrafish after exposure to low concentration of arsenite. (November 2018) - Dong, Wen-Qi; Sun, Hong-Jie; Zhang, Yu; Lin, Hong-Jun; Chen, Jian-Rong; Hong, Hua-Chang
Abstract: Low concentrations of arsenic (As) contamination in aquatic environment is a worldwide issue, which is of great concern. To evaluate the impact of low concentrations of As on zebrafish, we measured the growth, antioxidant enzymes including superoxide dismutase (SOD) and catalase (CAT), oxidative damage (malondialdehyde, MDA) and apoptosis-related genes ( nrf2, p53 and c-jun ) of adult zebrafish after exposing to different AsIII concentrations (0, 10, 50, 100 or 150 μg L −1 ) for 28 d. Results indicated that exposure to low AsIII concentrations decreased the zebrafish weight by 14%, increased the activities of SOD and CAT by 23–41% and 31–59%, decreased the contents of MDA by 29–54%, and modulated transcription of apoptosis related genes. Our study showed that chronic exposure to AsIII concentrations <150 μg L −1 generated oxidative stress and damage on zebrafish, and altered apoptosis-related genes in zebrafish. Graphical abstract: Image Highlights: Our study demonstrated the toxic effect of low concentrations of arsenite on zebrafish. Exposure to low concentration arsenite can decrease the growth of zebrafish. Exposure to low concentration arsenite can cause oxidative stress and damage on zebrafish. Exposure to low concentration arsenite can disrupt the transcriptional levels of apoptosis-related genes ( nrf2, p53 and c-jun ).